2011
DOI: 10.1002/asia.201100375
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Silicon Nanoparticles by Means of Thiol‐Ene Click Chemistry

Abstract: The preparation and characterization of butylene‐terminated silicon nanoparticles (SiNPs) and their functionalization using thiol‐ene chemistry is described, as well as the coupling of DNA strands. Bromide‐terminated SiNPs were prepared by means of the oxidation of magnesium silicide and functionalized with butylene chains through treatment with the corresponding Grignard reagent. The successful coupling was confirmed by NMR and FTIR spectroscopy. TEM measurements revealed a silicon‐core diameter of (2.4±0.5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 99 publications
2
92
0
Order By: Relevance
“…2,3 More versatile surface engineering and customisable organic termination can be achieved by chemical synthesis, [8][9][10][11] which also could allow for macroscopic production yields of Si-QDs. 12 In this case, alkylchains are good candidates for surface passivation, stabilizing it, preventing photo-oxidation (owing to formation of a strong covalent Si-C bond), and averting aggregation in solution.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 More versatile surface engineering and customisable organic termination can be achieved by chemical synthesis, [8][9][10][11] which also could allow for macroscopic production yields of Si-QDs. 12 In this case, alkylchains are good candidates for surface passivation, stabilizing it, preventing photo-oxidation (owing to formation of a strong covalent Si-C bond), and averting aggregation in solution.…”
Section: Introductionmentioning
confidence: 99%
“…8 SiQDs with mean diameter (2.2 ± 0.5) nm, are butyl capped and deposited densely on quartz substrate by drop-casting. Exclusion of oxygen on the SiQD surface was assured by careful synthesis of SiQDs in argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of silicon quantum dots, detection of small molecule analytes have been achieved, such as TNT [135], dopamine [136], and certain metal ions [137], while measurement of macromolecular activities was seen only recently [138]. Cheng et al showed that attaching a short dye labelled peptide to silicon quantum dots, with thiol-ene 'click' chemistry allowed the generation of FRET between silicon quantum dots and the dye whose intensity is enzyme responsive [101,139,140]. By this way they were able to for the first time control the surface to allow measurement of protease activity using colloidal silicon quantum dots.…”
Section: Bio-applicationsmentioning
confidence: 99%